2010
DOI: 10.1007/s10549-009-0723-4
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between the hOGG1 Ser326Cys polymorphism and breast cancer risk: evidence from 11 case–control studies

Abstract: The functional Ser326Cys polymorphism in the human 8-oxogunaine DNA glycosylase (hOGG1) gene has been implicated in breast cancer risk. However, the published findings are inconsistent. We therefore performed a meta-analysis to investigate this relationship. Eleven published case-control studies, including 6,804 breast cancer cases and 6,725 controls were identified. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the strength of the association. Overall, no significant associations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 23 publications
(35 reference statements)
1
21
0
Order By: Relevance
“…These results were discussed by Ding et al [28] , who combined all of the studies on European populations and performed a new meta-analysis, which indicated a lack of association between the OGG1 326Cys allele and BC risk for this ethnicity. This result was confirmed by the metaanalysis performed by Gu et al [29] , who identified 11 casecontrol studies published from 2003 to 2009; however, they did not observe any significant association between Ser326Cys SNP and BC risk, even in the analyses stratified by ethnicity, source of controls and menopausal status. An additional case-control study not included in the aforementioned meta-analysis also showed a lack of association between the OGG1 Ser326Cys variant and BC susceptibility [30] .…”
supporting
confidence: 54%
See 2 more Smart Citations
“…These results were discussed by Ding et al [28] , who combined all of the studies on European populations and performed a new meta-analysis, which indicated a lack of association between the OGG1 326Cys allele and BC risk for this ethnicity. This result was confirmed by the metaanalysis performed by Gu et al [29] , who identified 11 casecontrol studies published from 2003 to 2009; however, they did not observe any significant association between Ser326Cys SNP and BC risk, even in the analyses stratified by ethnicity, source of controls and menopausal status. An additional case-control study not included in the aforementioned meta-analysis also showed a lack of association between the OGG1 Ser326Cys variant and BC susceptibility [30] .…”
supporting
confidence: 54%
“…Ser326Cys 4 There was a lack of association between this SNP and BC risk in a European population Gu et al [29] …”
Section: Ogg1mentioning
confidence: 99%
See 1 more Smart Citation
“…However, no significant association between the OGG1 326Cys allele and breast cancer was found among Asian women (Yuan et al, 2010). Additionally, another meta-analysis of OGG1 Ser326Cys, which included data from 11 studies, also failed to observe an association between OGG1 Ser326Cys and breast cancer risk in the in European or Asian subjects or in an analysis stratified by ethnicity, source of control subjects, and menopausal status (Gu et al, 2010). We found that OGG1 Ser326Cys conferred a significant protective effect against breast cancer among women having a low BMI (< 24 kg/m 2 ) and the OGG1 Ser/Cys genotype (P = 0.027) or OGG1 Cys/Cys genotype (P = 0.005).…”
Section: Discussionmentioning
confidence: 99%
“…We have also read with great interest the recent metaanalysis by Gu et al [6], the study of Gu et al [6] had eleven case-control studies, and the results suggest that no significant associations between the hOGG1 Ser326Cys polymorphism and breast cancer risks were observed in all genetic model. And in the stratified analysis by ethnicity, no significant results were observed in European population (Cys/Cys vs. Ser/Ser: OR = 0.93, 95% CI = 0.77-1.13; dominant model: OR = 0.96, 95% CI = 0.88-1.05), which is consistent with our findings.…”
Section: To the Editormentioning
confidence: 96%